Early life stress unravels epistatic genetic associations of cortisol pathway genes with depression - Pereira, Sherliane Carla; Coeli-Lacchini, Fernanda Borchers; Pereira, Daniela Alves; Ferezin, Letícia Perticarrara; Menezes, Itiana Castro; Baes, Cristiane von Werne; Luizon, Marcelo Rizzatti; Juruena, Mario F.; Cleare, Anthony J.; Young, Allan H.; Lacchini, Riccardo (Journal of psychiatric research, 2024)
Dysregulation of the hypothalamic-pituitary-adrenal (HPA) axis represents one of the most consistent pathophysiological findings in depressive disorders. Cortisol signaling is affected by proteins that mediate its cellular responses or alters its availability to mineralocorticoid and glucocorticoid receptors. In our study, we evaluated candidate genes that may influence the risk for depression and suicide due to its involvement in cortisol signaling. The aim of the study was to assess whether the genotypes of these genes are associated with the risk for depression, severity of depressive symptoms, suicidal ideation, and suicide attempts. And whether there is interaction between genes and early-life stress. In this study, 100 healthy controls and 140 individuals with depression were included. The subjects were clinically assessed using the 21-item GRID-Hamilton questionnaires (GRID-HAMD-21), Beck Scale for Suicidal Ideation (BSI), and the Childhood Trauma Questionnaire (CTQ). A robust multifactorial dimensionality reduction analysis was used to characterize the interactions between the genes HSD11B1, NR3C1, NR3C2, and MDR1 and early-life stress. It was found a significant association of the heterozygous genotype of the MDR1 gene rs1128503 polymorphism with reduced risk of at least one suicide attempt (OR: 0.08, p = 0.003*) and a reduction in the number of suicide attempts (β = −0.79, p = 0.006*). Furthermore, it was found that the MDR1 rs1228503 and NR3C2 rs2070951 genes interact with early-life stress resulting in a strong association with depression (p = 0.001). Our findings suggest that polymorphisms in the MDR1 and NR3C2 genes and their interaction with childhood trauma may be important biomarkers for depression and suicidal behaviors.